The ancient mariners : seafarers and sea fighters of the Mediterranean in ancient times - Casson, Lionel, 1914-2009 (Princeton University Press, 1991)
Tells the story of ancient accomplishments on the sea from the earliest times to the end of the Roman Empire, explaining how seafaring people perfected trading vessels from mere rowboats into huge freighters that could carry over a thousand tons, how they transformed warships from simple oared transports into complex rowing machines holding hundreds of marines and even heavy artillery, and how their maritime commerce progressed from short cautious voyages to a network that reached from Spain to India.